Yield and chemical composition of CT-115 (Pennisetum purpureum) pasture established at two densities and in two sowing dates in Mar?n, Nuevo Le?n, Mexico - Nava, J. J.; Guti?rrez, E.; Herrera, Rafael Segundo; Zavala, F.; Olivares, E.; Trevi?o, J. E.; Bernal, H.; Vald?s, C. G. S. (Cuban Journal of Agricultural Science, 2013)
The yield and content of nutrients was assessed in leaves, stems and dead material of Pennisetum purpureum cv. Cuba CT-115 sown at two densities (D1=17850 and D2=11350 plants/ha) and on two sowing seasons (late and early) in the northeast of Mexico. The sowing was conducted considering a completely random design, with factorial arrangement 2 x 2 x 3 and on July-August (early season) and September- October (late season) of 2009. Sixteen experimental plots in a total area of 900 m2 were used. Seven sprouts per experimental unit were randomly sampled, 45 d after the regrowth during May of 2010. The variables were yield (t/ha), cell content, CP, NDF, ADF, hemicellulose and in vitro organic matter digestibility. The production of leaf, stem and dead material (t/ha) had significant differences (P < 0.01) and the values were 2.65, 1.84 and 0.74, respectively. The CP content was higher (P < 0.05) in leaf and stem (11.3 and 10.04 %) compared with the dead material (6.01 %). The ash content was higher (P < 0.05) in both sowing seasons, with range between 14.5-20.9 % for the different morphological components. The digestibility was of 63.6 %. It is concluded that the pasture CT-115 (Pennisetum purpureum) had good quality and may be considered an alternative for cattle feeding in the northeast of Mexico. Key words: Pennisetum purpureum CT 115, chemical composition, sowing density, sowing date, dry matter production.